Swallowing function after acute ischemic stroke: Development and validation of a novel clinical prognostic model - Zhang, Peiliang; Zhang, Wenbo; Shi, Wujie; Weng, Jianbin; Zhang, Zhongyuan; Lin, Chao; Wang, Ning; Shen, Zhipeng; Chen, Zhi-Lin (Frontiers in Nutrition, 2022)
Background: Predicting the duration of dysphagia after acute ischemic stroke (AIS) is important for clinical treatment decisions. Objective: The purpose of this study is to assess the swallowing function of AIS patients and to develop and validate a prognostic model for the need for nasogastric tube (NGT) in these patients. Materials and methods: We included 554 AIS patients during 2018-2019 as the development group and had 186 AIS patients as the external validation group. The primary end point of the study was the retention of NGT in patients one week after admission (Functional Oral Intake Scale ≤ 4). Swallowing function and stroke-associated pneumonia (SAP) at one month post-onset were also the objectives of this study. The volume-viscosity swallow test (V-VST) was used to assess the patient's impaired swallowing function. The Predictive model was built by logistic regression. Results: Overall, a total of 104 patients required indwelling NGT at one week of AIS onset in development group. The final prognostic model includes 5 variables: age (OR:1.085, 95%CI:1.049-1.123), neutrophil-to-lymphocyte ratio (NLR) (OR:1.332, 95%CI:1.090-1.626), NIHSS (OR: 1.092, 95%CI:1.025-1.164), history of drinking (OR:2.532, 95%CI:1.452-4.417) and stroke location (Subtentorial vs. Supratentorial, OR:1.954, 95%CI: 1.088-3.509). The prediction model had an AUC of 0.810, while the external validation group was 0.794. Conclusion: In stroke patients, it is very important to decide early whether to indwell a NGT. The nomogram will support decision making for NGT insertion and help these patients recover from their condition.